Dinâmica da biomassa aérea e remanescente em área de plano de manejo na Floresta Tropical Seca, Caatinga - Lopes, José Frédson Bezerra (2018)
The timber management field in the tropical dry forest (TDF-caatinga) grew around 450% in the last two decades. Currently, a lumber cycle of 15 years is adopted, with suggestions to decrease it to 12 years in the State of Ceará, Brazil. In this work, however, we test the hypothesis that a period of 15 years is enough to have a sustainable management of the scrubs and tree biomass removal in TDF-caatinga under tree harvesting. In order to test this hypothesis, we investigated the dynamics of biomass as well as the vegetation structure throughout time in an area that was submitted to tree havesting. The trees protected by law were kept. The study occurred from January to March/2018 in the agrosilvopastoral management “Assentamento Ramalhete”, County of General Sampaio, Ceará, Brazil. The experimental arrangement consisted of completely randomized blocks with 6 (six) different treatments (vegetations cut 3, 5, 8, 11 and 15 years ago and VReg_40) with 7 (seven) replications. All plants were classified and we considered in this study those with perimeter at breast height (PBH) ≥ 6 cm. The following variables were chosen: Biomass of wood plants, absolute density, average annual biomass increase (ABI) and total aboveground biomass (alive+dead). Remaining biomass (branches) quantification occurred in 7 (seven) plots (1.0 x 1.0 m) over the strip in an area with recently cut vegetation. Also, we determined the strains biomass, which were considered as remaining biomass as well. To evaluate the influence of time over the vegetation, the MANOVA, ANOVA and the Kruskal-Wallis tests were applied. As for the remaining biomass (branches+strains), the means were compared by the “t” test. It was observed that, 15 years after the deforestation, the studied plot of TDF-caatinga presented wood plant biomass, absolute density and a plant distribution by diameter class similar to VReg_40 with, however, the predominance of only one pioneer species (Croton blanchetianus). This fact identifies a possible loss of biodiversity in the vegetation. After the cutting, it was identified a significant increase in the amount of residue (branches) to the soil, 18 Mg ha-1. This productivity is three times bigger than natural litter productivity. Another 3,43 Mg ha-1 stayed in the area as strains. We identified, also, that the VReg_40 had not yet recovered from the impact of human action (crops and livestock), since a predominance in the area of only two vegetation species occurred: one pioneer (Croton blanchetianus) and the other secondary (Cordia oncocalyx). We believe that the thinning management can be used instead of cutting in order to stimulate the presence of key-species and increase pasture production. Based on our results, we recommended studies in relation to thinned vegetation, pioneer species partial control, bank of native species seed bank as management strategies to improve the key species and biomass productivity. Since rainfall is a determinate factor in the regeneration process of vegetation and the average annual rainfall of the area is 42% bigger than that of other counties in the state of Ceará, we recommend that investigations should be done in others areas as well.